Effects of bundling policy on project cost under market uncertainty: A comparison across different highway project types. (December 2019) - Qiao, Yu; Fricker, Jon D.; Labi, Samuel
Abstract: As highway agencies seek project delivery strategies that can help minimize their overall costs, interest in the practice of project bundling, which refers to the combining of multiple projects of similar or different work types into a single contract, continues to increase. The past literature contains studies about the effects of bundling, particularly from a conceptual perspective, but with only minimal quantitative analysis of empirical data from past bundling projects. Past researchers hypothesized that the magnitude and direction of the effects of bundling policies on project cost differ not only across different market conditions but also across different highway project types. In seeking to test this hypothesis, this paper presents analysis that utilized past project cost data to verify the effects of these project-related and bundling-related factors on bundling outcomes. In the analysis that quantified the extent to which increasing the bundle size causes a reduction in the bidding competition, it was determined that this outcome varies across the different project types. In addition, using Monte Carlo simulation, the study established the bundle size threshold (the bundle size beyond which the project cost increases) and quantified the uncertainties associated with cost estimates that arise from varying bidding competition conditions; these were also found to vary across the different project types. The models introduced in this paper can be used by highway agencies at the early (planning) stages of development of a given project type, to predict the expected project award cost for different bundling alternatives and under different market uncertainties. Heightened awareness of the cost consequences across the different bundling policies, bidding market conditions, and project types can provide guidance to agencies that seek to establish or update project bundling policies.